2015
DOI: 10.1002/anie.201504962
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt(II)‐Catalyzed CH Alkynylation/Annulation with Terminal Alkynes: Selective Access to 3‐Methyleneisoindolin‐1‐one

Abstract: A highly efficient cobalt(II)-catalyzed alkynylation/annulation of terminal alkynes assisted by an N,O-bidentate directing group is described. This protocol is characterized by wide substrate scope utilizing cheap cobalt catalysts, and offers a new approach to 3-methyleneisoindolin-1-one, which can be converted into an oxadiazine salt in one step. Moreover, the directing group could be removed in three steps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(49 citation statements)
references
References 53 publications
1
47
1
Order By: Relevance
“…The double bond configuration in the major diastereomer was proven by crystal structure analyses and is in accord with the 1 H NMR shift of one strongly shielded C ar ‐H at δ =6.3–6.4 ppm (see the Supporting Information). The high double bond selectivity contrasts with previously reported results for the Co II ‐catalysed alkynylation/annulation of acetamides where preferentially the ( Z )‐isomers were formed . The structures of all new compounds reported herein were determined by single‐crystal X‐ray diffraction methods (Figure 1–; all data and CCDC numbers are given in the Supporting Information).…”
Section: Resultscontrasting
confidence: 62%
“…The double bond configuration in the major diastereomer was proven by crystal structure analyses and is in accord with the 1 H NMR shift of one strongly shielded C ar ‐H at δ =6.3–6.4 ppm (see the Supporting Information). The high double bond selectivity contrasts with previously reported results for the Co II ‐catalysed alkynylation/annulation of acetamides where preferentially the ( Z )‐isomers were formed . The structures of all new compounds reported herein were determined by single‐crystal X‐ray diffraction methods (Figure 1–; all data and CCDC numbers are given in the Supporting Information).…”
Section: Resultscontrasting
confidence: 62%
“…In addition to the above six‐membered ring products, the five‐membered ring products could also be obtained by similar C−H activation/annulations reactions. In 2015, Niu and Song reported a highly efficient Co II C 2 O 4 ⋅ 4 H 2 O‐catalyzed alkynylation/annulation assisted by an N,O‐bidentate directing group (PyO) 86 with terminal alkynes 87 (Scheme ) …”
Section: C−h Activation/functionalizations Catalyzed By Using Coii Amentioning
confidence: 99%
“…Recently,t he groups of Daugulis, [6] Ackermann, [7] and others [8] have shown that air-stable commercially available Co II /Co III salts can be used to functionalize aromatic/vinylic C(sp 2 )ÀHbonds with alkynes/alkenes.Cobalt-catalyzed CÀH activation reactions of amides with alkenes afforded the [4+ +2] or [4+ +1] annulation products (Scheme 1). Considering the hypothesis that these reactions proceed through directing group (DG) assisted C À Ha ctivation, alkene insertion, and Scheme 1.…”
mentioning
confidence: 99%